Arsitektur Enterprise Sistem Informasi E-Commerce untuk Pemasaran Hasil Pertanian - Tarwoto; Serli; Syawalia Rahayu; Zanela Anania; Amanda Ayu Novitasari (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This research aims to design enterprise architecture to support the implementation of e-commerce information systems in agricultural product marketing. By utilizing the Extreme Programming (XP) approach as a development method, this system is expected to facilitate the marketing of agricultural products directly between farmers and consumers, and overcome the problems in the long and inefficient distribution chain. The designed enterprise architecture coordinates various system components, including customer data, inventory management, transaction processes, logistics, and sales data reporting. The system consists of several main views, such as Home, Login, Register, and Chart pages, which are designed to facilitate user and farmer interaction in conducting transactions. With a flexible and adaptive approach, this research is expected to support the sustainability of the agricultural sector through an inclusive e-commerce system, increase the accessibility of agricultural product marketing, and empower farmers economically.